Impact of Reforms on Operational Performance of Selected Public Sector Banks (International Journal of Innovative Research in Engineering & Management, 2023)
People's need for a safe place to deposit  money led to the development of commercial banking. It  didn't require a lot of investment for the individuals who held  others' overflow cash to understand that their business could  be made productive assuming they loan out again what was  gotten by them, given that it was returned when it was  required. The banking business is comprised of borrowing  and lending, which are the bank's two primary functions. The  modern banker performs numerous other duties in addition  to these two fundamental ones. The following are the roles  that commercial banks play namely Accepting Deposits,  Advancing Loans, and Other Services.
Keywords: Public Sector Banks; Accepting Deposits; Advancing Loans; Banking Business